1992
DOI: 10.1111/j.1365-2303.1992.tb00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Borderline Nuclear Abnormality In Cervical Smears

Abstract: Women with cervical smears showing borderline nuclear abnormality (BNA), or reactive changes in the form of squamous metaplasia (SM) or endocervical cell hyperplasia (ECH), were age-matched with healthy controls to determine the outcome of these conditions. No significant difference in the risk of dyskaryosis was observed in cases showing reactive changes and the controls. In contrast, there was a 23% excess of cases showing dyskaryosis in the repeat smears of cases of BNA over the controls. An odds ratio of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…8 This study indicates that 10.2% of women developed a high grade dyskaryosis or CIN lesion within two years of having a borderline smear. Hirschowitz et al found that 22.4% of women with borderline cytological changes had a smear test showing high grade dyskaryosis which developed between 13 and 106 months after the index smear.…”
Section: Discussionmentioning
confidence: 69%
“…8 This study indicates that 10.2% of women developed a high grade dyskaryosis or CIN lesion within two years of having a borderline smear. Hirschowitz et al found that 22.4% of women with borderline cytological changes had a smear test showing high grade dyskaryosis which developed between 13 and 106 months after the index smear.…”
Section: Discussionmentioning
confidence: 69%
“…Initial attempts to standardize reporting systems recognized that cases arise where there is genuine doubt as to the reactive or neoplastic nature of cellular changes, and included categories which expressed that doubt, naming them borderline or Atypical Squamous Cells of Undetermined Significance (ASCUS) 2,6 . Although subject to substantial inter‐ and intra‐observer variability, these cases yielded rates of dyskaryosis of 23–38% on follow‐up 7–10 . However, these categories did not specify the nature of the diagnostic problem in an individual case.…”
Section: Introductionmentioning
confidence: 99%
“…2,6 Although subject to substantial inter-and intraobserver variability, these cases yielded rates of dyskaryosis of 23-38% on follow-up. [7][8][9][10] However, these categories did not specify the nature of the diagnostic problem in an individual case. In particular, they did not segregate that group of conditions featuring atypical cells with a high nuclear-cytoplasmic ratio, suspicious but not meeting the criteria for high-grade dyskaryosis or even invasive carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The problem is compounded by the fact that few long term studies have been done which define the risk of developing cervical intraepithelial neoplasia (CIN) or cancer in women identified as having borderline nuclear changes in their cervical smears. 6 The natural tendency in reporting smears is, therefore, to err on the side of caution and, if there is any doubt about the clinical importance of changes in a smear, to report borderline nuclear changes, thus ensuring that a follow up smear will be done within a relatively short period of time.…”
Section: Introductionmentioning
confidence: 99%